2010
DOI: 10.1111/j.1742-4658.2010.07673.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights into structure–function relationships of oxalyl CoA decarboxylase from Escherichia coli

Abstract: DatabaseStructural data for holo-EcODC (ThDP-EcODC) in the absence of additional ligands and in complex with either ADP or acetyl CoA have been submitted to the Protein Data Bank under the accession numbers 2q27, 2q28 and 2q29, respectively. The gene yfdU from Escherichia coli encodes a putative oxalyl coenzyme A decarboxylase, a thiamine diphosphate-dependent enzyme that is potentially involved in the degradation of oxalate. The enzyme has been purified to homogeneity. The kinetic constants for conversion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…we also found that other OTUs-such as some members of the families S24-7, Helicobacter, and Lachnospiraceae-are more positively affected by oxalate consumption than these well-known oxalate degraders (Tables 1 and 2). One possible explanation is that these taxa have uncharacterized oxalate degrading capacity or homologs of oxalyl-CoA decarboxylase (Sahin, 2003;Werther et al, 2010). Even in strains isolated from N. albigula, Miller et al, (2014) find species that can degrade oxalate in vitro may lack the oxalyl-CoA decarboxylase gene.…”
Section: Resultsmentioning
confidence: 99%
“…we also found that other OTUs-such as some members of the families S24-7, Helicobacter, and Lachnospiraceae-are more positively affected by oxalate consumption than these well-known oxalate degraders (Tables 1 and 2). One possible explanation is that these taxa have uncharacterized oxalate degrading capacity or homologs of oxalyl-CoA decarboxylase (Sahin, 2003;Werther et al, 2010). Even in strains isolated from N. albigula, Miller et al, (2014) find species that can degrade oxalate in vitro may lack the oxalyl-CoA decarboxylase gene.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, for MAP3651c, template 2CX9 was modeled by SWISS-MODEL Workspace and template 2PGO (L. Chen et al, unpublished data) was modeled by ElliPro. The MAP3523c protein was also modeled with two different templates, 2Q29 (39) by SWISS-MODEL Workspace and 2Q27 (39) by ElliPro, from the crystal structure of oxalyl-coenzyme A (oxalyl-CoA) decarboxylase from E. coli. The details of the 3D structure template IDs and the descriptions of the source molecules are shown in Table S3 in the supplemental material.…”
Section: Resultsmentioning
confidence: 99%
“…Others, such as ␣-ketoglutarate dehydrogenase and 2-hydroxy-3-oxoadipate synthase, are allosterically activated by binding of a small molecule (acetyl-CoA) to a shallow pocket on the enzyme surface and allosterically inhibited by binding of a regulatory protein (GarA) (40 -42). Similarly, pyruvate decarboxylase (43), phenylpyruvate decarboxylase (17,18), and oxalyl-CoA decarboxylase (21) have all been shown to be positively regulated by the direct binding of small molecules to domain II.…”
Section: Regulatory Variation In the Thdp-dependent Enzyme Superfamilymentioning
confidence: 99%